2021
DOI: 10.1186/s40068-021-00232-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental implications of soil erosion and sediment yield in Lake Hawassa watershed, south-central Ethiopia

Abstract: Background Assessing soil erosion, sediment yield and sediment retention capacity of watersheds is one of the under-researched areas in watersheds of developing countries like Lake Hawassa watershed. The study examined soil erosion and sediment yield and their environmental implications in the Lake Hawassa watershed. The quantification and mapping were carried out using the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model. Data such as Land Use Land Cover (LULC), Digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 85 publications
3
19
2
Order By: Relevance
“…At the same time, evergreen forest generated the lowest average sediment export, with a value of 0.01 tons/km 2 , in the Klong U-Tapao watershed, Songkhla Province, Thailand. Likewise, Degife et al [74] found that the highest sediment export per unit of area was observed from miscellaneous land (bare land), while the highest contribution of the total sediment that reached the surrounding water bodies was from cultivated land (40.7%). Similarly, Zhou et al [75] found that decreases in miscellaneous land (bare land) significantly reduced sediment export in the Qiantang River Basin, China.…”
Section: Sediment Export Estimationmentioning
confidence: 95%
See 1 more Smart Citation
“…At the same time, evergreen forest generated the lowest average sediment export, with a value of 0.01 tons/km 2 , in the Klong U-Tapao watershed, Songkhla Province, Thailand. Likewise, Degife et al [74] found that the highest sediment export per unit of area was observed from miscellaneous land (bare land), while the highest contribution of the total sediment that reached the surrounding water bodies was from cultivated land (40.7%). Similarly, Zhou et al [75] found that decreases in miscellaneous land (bare land) significantly reduced sediment export in the Qiantang River Basin, China.…”
Section: Sediment Export Estimationmentioning
confidence: 95%
“…Annual land requirements under Scenario III for each LULC type.As a result, under Scenario III, economic crop areas, precisely paddy field, field crop, para rubber, and perennial trees and orchards were located based on suitability classes of economic crop zonation. Paddy fields expanded from 220 74. km 2 in 2019 to 280.20 km 2 in 2029, and field crop areas increased from 21.84 km 2 in 2019 to 34.11 km 2 in 2029.…”
mentioning
confidence: 99%
“…A study done in the Northern Gojam sub-basin by [59] ascertained that agricultural land had exhibited a gross increase of 17.2% between 1994-2007. Findings by many other scholars at different temporal and spatial dimensions have put forward similar results [56,[60][61][62]. High population growth and the emerging landless youth have forced the community to plough forest, area closures and grazing lands.…”
Section: Discussionmentioning
confidence: 56%
“…It is inevitable to observe LULCC occurring in non-linear form due to complex and interweaved anthropogenic and natural processes. Transformation of land is a trend that will continue to unfold, as most of the intervention was raised from the very egocentric nature of human beings and their descendants [56][57][58]. Ever since the history of humanity, land devoted to human use has grown considerably, and increases in the production of commodities have further accelerated the use and abuse of land resources [51].…”
Section: Discussionmentioning
confidence: 99%
“…128 However, the USLE/RUSLE was applied at different parts of Ethiopia following similar 129 or different approaches to estimate any of its factors (e.g, [28,[33][34][35][36][37][39][40][41][42][43][44]46,48]).…”
Section: Introductionmentioning
confidence: 99%